Macrobenthic Surf Zone Community of Temperate Sandy Beaches: Spatial and Temporal Patterns - Carcedo, Maria Cecilia (2015)
The spatial and temporal patterns within the surf zone epibenthic assemblages were studied in a coastal fringe of Argentina to determine whether assemblage compositions, abundance, species richness and diversity vary spatially and temporarily. Sampling was conducted seasonally in two sandy beaches over 2 years with a benthic sledge used to collect the fauna in the upper centimeters of soft bottom sediments and the epifauna on the sediment surface. Physical variables were measured in the same coastal sites where biological sampling was conducted. A total of 58 morphospecies were collected. Peracarid crustaceans were the most abundant group. The mysid Pseudobranchiomysis arenae (new genus–new species) (29.73 ± 17.79 ind. per sample) and the isopod Leptoserolis bonaerensis (51.54 ± 22.35 ind. per sample) were the most abundant and common species and were present regularly throughout the sampling period. Differences in the surf zone community composition were found between the beaches; these differences could be related to variation in physical parameters such as sand grain size and wave climate, indicating the possible influence of the morphodynamic state of the beaches on the epibenthic assemblages. A seasonal abundance trend was detected, reflecting the changes in abundance of the two dominant species; the richness pattern was not easily detectable due to the sporadic appearance of non-resident species in the surf zone, probably due to different causes, including dispersion by entry of water from surrounding areas, littoral currents and storms. The surf zone studied presents a complex and dynamic epibenthic community that appears to be influenced by the morphodynamic state of the beach and the dynamic of non-resident species.